Mechanisms of the Quorum Sensing Systems of Pseudomonas aeruginosa: Host and Bacteria - Flores-Percino, Diana; Osorio-Llanes, Estefanie; Sepulveda, Yanireth; Castellar- López, Jairo; Madera, Ricardo Belón; Rada, Wendy R.; Meléndez, Carlos Mario; Mendoza-Torres, Evelyn (Current Medicinal Chemistry, 2024)
Quorum-sensing is a communication mechanism between bacteria with the ability to activate signaling pathways in the bacterium and in the host cells. Pseudomonas aeruginosa is a pathogen with high clinical relevance due to its vast virulence factors repertory and wide antibiotic resistance mechanisms. Due to this, it has become a pathogen of interest for developing new antimicrobial agents in recent years. P. aeruginosa has three major QS systems that regulate a wide gene range linked with virulence factors, metabolic regulation, and environment adaption. Consequently, inhibiting this communication mechanism would be a strategy to prevent the pathologic progression of the infections caused by this bacterium. In this review, we aim to overview the current studies about the signaling mechanisms of the QS system of P. aeruginosa and its effects on this bacterium and the host.
Keywords: virulence genes